2020
DOI: 10.3390/met10121584
|View full text |Cite
|
Sign up to set email alerts
|

Manufacturing and Study of Mechanical Properties, Structure and Compatibility with Biological Objects of Plates and Wire from New Ti-25Nb-13Ta-5Zr Alloy

Abstract: A Ti–25Nb–13Ta–5Zr alloy was produced and studied in this work, and plates and wires were made from this alloy. It is shown that the Ti–25Nb–13Ta–5Zr alloy has the required mechanical properties and a β-crystal phase. Microstructures were present on the surface of the alloy with a height of several hundred nm, located at a distance of 1.5–2 μm from each other. Ti–25Nb–13Ta–5Zr was superior to nitinol in terms of the formation of long-living reactive protein species and the generation of reactive oxygen species… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 54 publications
1
11
0
Order By: Relevance
“…It was found that cells growing on the TiNbTaZn medical alloy and on the AP-ZnO material have similar growth and development indicators. It should be noted that alloys based on TiNbTaZn are quite modern and advanced alloys [ 73 , 74 ]. It was shown that alloys based on TiNbTaZn have better characteristics than the widely used alloy nitinol [ 75 ].…”
Section: Discussionmentioning
confidence: 99%
“…It was found that cells growing on the TiNbTaZn medical alloy and on the AP-ZnO material have similar growth and development indicators. It should be noted that alloys based on TiNbTaZn are quite modern and advanced alloys [ 73 , 74 ]. It was shown that alloys based on TiNbTaZn have better characteristics than the widely used alloy nitinol [ 75 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although Ti–6Al–4V alloy is widely used as a structural material for implants, sometimes it has the tendency to generate problems, such as stress shielding and cytotoxicity that is mainly attributed to the presence of vanadium. Hence, it should be pointed out that other Ti-base alloys are also being considered as of late, such as beta-type Ti–Nb–Zr–Mn alloys [ 15 ], Ti25Nb–13Ta–5Zr [ 16 ], and Ti–Al–Nb [ 17 ]. As for the infiltrated biodegradable metal, there are basically three common alternatives: Fe-base, Mg- base, and Zn-base alloys.…”
Section: Introductionmentioning
confidence: 99%
“…In low elastic modulus Ti-Nb-Sn alloys, the Sn content does not exceed 4 wt./wt.% [ 64 , 65 ]. In contrast, the Zr content of low elastic modulus Ti-Nb-Ta-Zr alloys (55–60 GPa) is in the range of 4.5–7.0 wt./wt.% [ 66 , 67 , 68 ], an example, Ti-29Nb-13Ta-4.6Zr ([Mo]eq = 10.7) [ 3 , 69 , 70 ]. A shortcoming of this alloy is its relatively high cost due to the high content of Ta.…”
Section: Methodsmentioning
confidence: 99%